PENGARUH MEDIA SOSIAL WHATSAPP TERHADAP KINERJA GURU DI MASA PANDEMI COVID-19 - Suyit Ratno; Rizki Aulia Elissa (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This research aims to determine whether the use of WhatsApp social media during the Covid19 pandemic has an effect on teacher performance at UPT SPF SD Negeri 101877 Tanjung Morawa. The research method is a correlational research method. The subjects of this study were teachers at UPT SPF SD Negeri 101877 Tanjung Morawa in 2020/2021. The research sample was 20 teachers using the population research method. Data from this survey was collected through a questionnaire. The questionnaire used was tested for validity and reliability. While the data analysis method used is product moment correlation. Based on the calculation results obtained r count of 9.566, and these results are compared with r table at a significance level of 5% (2.086). This means that the use of WhatsApp social media affects the performance of teachers  UPT SPF SD Negeri 101877 Tanjung Morawa  during the covid19 pandemic. Meanwhile, the use of WhatsApp accounted for 69.1% of teacher performance, with the remaining 30.9% influenced by other factors.Keywords: WhatsApp social media, teacher performance, covid19 pandemic